2021
DOI: 10.3390/ijms222413390
|View full text |Cite
|
Sign up to set email alerts
|

JAK Inhibition Prevents DNA Damage and Apoptosis in Testicular Ischemia-Reperfusion Injury via Modulation of the ATM/ATR/Chk Pathway

Abstract: Testicular ischemia reperfusion injury (tIRI) causes oxidative stress-induced DNA damage leading to germ cell apoptosis (GCA). The aim of the study is to establish a direct link between JAK2 activation and the DNA damage response (DDR) signaling pathways and their role in tIRI-induced GCA using AG490, a JAK2 specific inhibitor. Male Sprague Dawley rats (n = 36) were divided into three groups: sham, unilateral tIRI and tIRI + AG490 (40 mg/kg). During tIRI, augmentation in the phosphorylation levels of the JAK2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that the expression of STAT3 was closely related to DNA damage [ 12 ]. In the above results, we found that the high-Trx1 HP can induce higher expression of p-STAT3, so we speculated that the high-Trx1 HP may result in stronger DNA damage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the expression of STAT3 was closely related to DNA damage [ 12 ]. In the above results, we found that the high-Trx1 HP can induce higher expression of p-STAT3, so we speculated that the high-Trx1 HP may result in stronger DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…The STAT3 signaling pathway is involved in regulating DNA transcription and gene expression and affects biological processes such as cell proliferation, differentiation, and apoptosis [ 11 ]. Besides, the previous studies have shown that the downregulation of STAT3 activity was related to the reduction of DNA damage, to maintain genome stability and protect against cell death [ 12 ]. It has been reported that as many as 70% of human tumors have abnormal enhancement of STAT3 activity, including gastric cancer, esophageal cancer, liver cancer, and other tumors [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To better characterize the molecular and 14 Oxidative Medicine and Cellular Longevity cellular events related to AKI, we used the TRAP-seq results in the GEO database to examine PLK3 expression in the translation profile of nephrons (tubules) exposed to IRI for 24 h. GO analysis showed that PLK3 was mainly involved in oxidative stress and DNA damage after renal I/R injury. DNA damage has been reported to be involved in I/R injury in a variety of vital organs, including the testicular, brain, liver, and heart [33][34][35][36]. During renal I/R injury, DNA fragmentation in the renal tubules after DNA damage occurs as early as 12 h after reperfusion and increases within 24 h [37].…”
Section: Discussionmentioning
confidence: 99%
“…Differently, myocardial infarction, stroke or testicular torsion are sudden, and the management can only occur during ischemia [ 7 ] and during blood reflow [ 8 ]. Despite the identification of many protective treatments in experimental models of I/R, their translation to the clinic has shown very disappointing benefits for patients, especially for stroke and infarct [ 9 , 10 ].…”
mentioning
confidence: 99%
“…The multiplicity of these processes involves numerous cellular mechanisms and pathways, which are all potential therapeutic targets. In this Special Issue, original approaches targeting various ubiquitous kinase pathways are proposed for testicular torsion and kidney transplantation [ 3 , 4 , 7 ], which could be extended to other ischemic events, as well as specific combinatory treatment using hormones in the case of uterus transplantation [ 5 ]. In the majority of ischemic situations, mitochondria play a central role as depletion in oxygen supply leads to the impairment of mitochondrial function and loss of energy metabolites, mainly following at the time of reperfusion by oxidative stress and disturbance of Ca 2+ homeostasis crucial for cell viability [ 1 , 13 ].…”
mentioning
confidence: 99%